Nurses’ Caring Behavior Based on Personality - Anita Sampe; Wirmando Wirmando; Lidya Gracelya Paulus; Margareta Sintia Puspita (Journal of Nursing Science Update (JNSU), 2023)
Psychological factors, including the characteristics of personality, influence caring behaviour. In this case, nurses can be assessed for their caring behaviour in nursing services through their personality characteristics. The characteristics of a nurse's personality influence the provision of the quality of nursing services carried out. This study aimed to determine the relationship between personality characteristics and hospital nurses' caring behaviour. A cross-sectional study was adopted involving 72 nurses of a Stella Maris Hospital in Makassar selected by purposive sampling. Data were collected from Caring Behavior Assessment (CBA) and Eysenck Personality Questionnaire (EPQ) test results. Statistical analysis used the chi-square test. The study indicated that most nurses were extroverts (66,7%) and had a caring attitude. Based on the chi-square statistical test, a value of p = 0.000 (α = 0.05) was obtained, meaning a significant relationship exists between personality characteristics and caring behaviour. Extrovert personality types care more compared to introvert personality types because their attitudes are intelligent in speaking, anxiety-free, not easily embarrassed, not awkward, friendly, gregarious, able to cooperate, adaptable, flexible, and usually conservative. Therefore, this study recommends hiring nurses who have extrovert characteristics.